Sarahisme Posted August 20, 2005 Posted August 20, 2005 is this a 'proof' for this question? [math] h(x) = \sqrt(3 + x) [/math] we want to find a K > 0 such that [math] |h(x) - h(y)| \leq K|x-y| \forall x,y \in [0,1] [/math] that is we want a K > 0 such that [math] |\sqrt(3 + x) - \sqrt(3 + y)| \leq K|x-y| \forall x,y \in [0,1] [/math] now [math] |\sqrt(3 + x) - \sqrt(3 + y)| [/math] [math] = frac{|(\sqrt(3 + x) - \sqrt(3 + y))(\sqrt(3 + x) - \sqrt(3 + y)|}{1} [/math]
Recommended Posts
Create an account or sign in to comment
You need to be a member in order to leave a comment
Create an account
Sign up for a new account in our community. It's easy!
Register a new accountSign in
Already have an account? Sign in here.
Sign In Now